The effect of range of motion (ROM) exercises on the occurrence of neuropathy and angiopathy in diabetes mellitus patients in the Medan Tuntungan Community Health Center area - Dameria Br Ginting; Herianto Bangun (International Journal of Health and Pharmaceutical (IJHP), 2025)
Ankle ROM training is a movement that includes 2 movements, namely dorsiflexion and plantarflexion which result in increased calf muscle strength and increased calf muscle pump thereby facilitating venous return which has a positive impact in facilitating the diffusion of oxygen and nutrients. By providing Active Lower ROM intervention to Diabetes Mellitus patients twice a day for 6 consecutive days at the same time. Statistically, it can be seen that there was an influence on the ABI and DNE values before the intervention was given and after the Active Lower ROM intervention was given. This type of research uses quasi-experimental research using two group pretest-posttest, namely an experimental design where there are control and intervention groups. The samples in this study were 35, of which 17 samples were for the intervention group and 18 samples were for the control group. Based on the results of the research, data obtained from the analysis of the effect of giving ankle ROM exercises on the DNE score and ABI value in the intervention group and the control group were, in the DNE score, the statistical test result was p = 0.000, and it can be believed that there is a significant difference between the DNE score of the intervention group. And the control group after doing ankle ROM exercises (p = 0.000 α = 0.05), then H0 was rejected or there was an effect of ROM exercises on reducing the risk of neuropathy. Meanwhile, the ABI value showed a statistical test result of p = 0.002 and it can be believed that there is significant difference between the ABI values of the intervention group and the control group after ankle ROM exercises (p = 0.002 α = 0.05), so H0 is rejected or there is an effect of ROM exercises on reducing the risk of Angiopathy.